Analisis sedimentasi terhadap umur guna Waduk Bili-Bili - Fachriadam, Muh; Musa, Ratna; Sar, Mas ud (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate the level of sedimentation that occurs and its impact on the reservoir capacity. The data used includes bathymetry measurements in 2023, drift and bottom sediment discharge, as well as historical sediment inflow data. Analysis was carried out to calculate sediment volume, sedimentation rate, and changes in reservoir capacity. The research results show that the Bili-Bili Reservoir experienced a significant reduction in storage capacity from 1997 to 2023. The total sedimentation that occurred reached 50 million cubic meters, reducing the storage capacity from 375 million cubic meters to 325 million cubic meters. The actual sedimentation rate of 1.5 mm per year exceeds the initial plan. This condition means that the useful life of the reservoir, which was originally designed for 50 years, is estimated to only be able to last up to 19 years of the remaining life of the existing reservoir, which is faster than the design plan life. This impact not only reduces flood control capacity but also reduces the effectiveness of water supply. standard for society. Recommendations from this research include implementing catchment area management with conservation techniques such as reforestation and land use control, increasing the frequency of sediment dredging in reservoirs, as well as using sediment control building technology to reduce the entry of sediment material into reservoirs. The results of this research provide relevant information for sustainable planning and management of reservoirs so that their function remains optimal in the future.